Peran Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru Dan Kualitas Pembelajaran IPAS Di SMKN 8 Kepulauan Selayar - Salmawati Salmawati; Hartini Hartini; Andi Mulyadi Radjab (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This article analyzes the role of the principal in improving teacher professionalism and the quality of IPAS learning at SMKN 8 Kepulauan Selayar. The manuscript was developed from a qualitative case study proposal and preliminary school observation data. The planned study involved six informants: a school supervisor, the principal, the vice principal, and three IPAS teachers. Data collection was designed through in-depth interviews, participatory observation, focus group discussion, school document analysis, and documentation. Preliminary findings identified several core problems: 61% of teachers had not joined innovative learning or Kurikulum Merdeka training in the last two years, IPAS learning mastery remained at 65-68% below the school target of 80%, lecture-based learning still dominated classrooms, digital media use was limited, and the local island context had not been optimally used as learning resources. The analysis shows that the principal should function as an academic supervisor, professional development facilitator, motivator, and manager of professional learning communities. Further empirical data collection is required to strengthen the final findings.